Оцінка успішності інтродукції та перспективності видів, різновидів і форм Pinus L. в умовах Києва - Marynych, I.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The results of study of successful introduction and availability of 27 species, varieties and forms of Pinus L. genus with using of integral numerical method are presented.